Accounting for poverty differences between the United States, Great Britain, and Germany - Biewen, Martin; Jenkins, Stephen (Discussion papers, 2002)
We propose a framework for comparing the relationship between poverty and personal characteristics across countries (or across years), and use it to compare levels and patterns of relative poverty in the USA, Great Britain and Germany during the 1990s. The higher aggregate poverty rates in the USA and in Britain relative to Germany were mostly accounted for by higher poverty rates conditional on characteristics, which were only partly offset by a more favourable distribution of poverty-relevant characteristics, in particular higher employment rates.
Keywords: Graue Literatur; Arbeitspapier